U.S. emissions of HFC‐134a derived for 2008–2012 from an extensive flask‐air sampling network. Issue 2 (23rd January 2015) - Hu, Lei; Montzka, Stephen A.; Miller, John B.; Andrews, Aryln E.; Lehman, Scott J.; Miller, Benjamin R.; Thoning, Kirk; Sweeney, Colm; Chen, Huilin; Godwin, David S.; Masarie, Kenneth; Bruhwiler, Lori; et al.
Abstract U.S. national and regional emissions of HFC‐134a are derived for 2008–2012 based on atmospheric observations from ground and aircraft sites across the U.S. and a newly developed regional inverse model. Synthetic data experiments were first conducted to optimize the model assimilation design and to assess model‐data mismatch errors and prior flux error covariances computed using a maximum likelihood estimation technique. The synthetic data experiments also tested the sensitivity of derived national and regional emissions to a range of assumed prior emissions, with the goal of designing a system that was minimally reliant on the prior. We then explored the influence of additional sources of error in inversions with actual observations, such as those associated with background mole fractions and transport uncertainties. Estimated emissions of HFC‐134a range from 52 to 61 Gg yr−1 for the contiguous U.S. during 2008–2012 for inversions using air transport from Hybrid Single‐Particle Lagrangian Integrated Trajectory (HYSPLIT) model driven by the 12 km resolution meteorogical data from North American Mesoscale Forecast System (NAM12) and all tested combinations of prior emissions and background mole fractions. Estimated emissions for 2008–2010 were 20% lower when specifying alternative transport from Stochastic Time‐Inverted Lagrangian Transport (STILT) model driven by the Weather Research and Forecasting (WRF) meteorology. Our estimates (for HYSPLIT‐NAM12) are consistent with annual emissions reported by U.S. Environmental Protection Agency for the full study interval. The results suggest a 10–20% drop in U.S. national HFC‐134a emission in 2009 coincident with a reduction in transportation‐related fossil fuel CO2 emissions, perhaps related to the economic recession. All inversions show seasonal variation in national HFC‐134a emissions in all years, with summer emissions greater than winter emissions by 20–50%.